Tunable Compact Narrow Band THz Sources for Frequency Domain THz Anisotropic Spectroscopy - George, D. K.; LaFave, T. J.; Markelz, A. G.; McNee, I.; Tekavec, P.; Kozlov, V.; Schunemann, P. (Conference on Next-Generation Spectroscopic Technologies XII, 2019)
We demonstrate frequency domain THz anisotropy signature detection for protein crystal models using newly developed compact tunable narrow band THz sources based on Orientation Patterned Gallium Phosphide for turn-key spectroscopic systems.
Keywords: anisotropy; biomolecules; femtosecond; optical rectification; orientation patterned gallium phosphide; Terahertz; THz generation